Low Microcirculatory Perfused Vessel Density and High Heterogeneity are Associated With Increased Intensity and Duration of Lactic Acidosis After Cardiac Surgery with Cardiopulmonary Bypass. Issue 2 (August 2021) - Greenwood, John C.; Jang, David H.; Spelde, Audrey E.; Gutsche, Jacob T.; Horak, Jiri; Acker, Michael A.; Kilbaugh, Todd J.; Shofer, Frances S.; Augoustides, John G.T.; Bakker, Jan; Abella, Benjamin S.
ABSTRACT: Introduction: Lactic acidosis after cardiac surgery with cardiopulmonary bypass is common and associated with an increase in postoperative morbidity and mortality. A number of potential causes for an elevated lactate after cardiopulmonary bypass include cellular hypoxia, impaired tissue perfusion, ischemic-reperfusion injury, aerobic glycolysis, catecholamine infusions, and systemic inflammatory response after exposure to the artificial cardiopulmonary bypass circuit. Our goal was to examine the relationship between early abnormalities in microcirculatory convective blood flow and diffusive capacity and lactate kinetics during early resuscitation in the intensive care unit. We hypothesized that patients with impaired microcirculation after cardiac surgery would have a more severe postoperative hyperlactatemia, represented by the lactate time-integral of an arterial blood lactate concentration greater than 2.0 mmol/L. Methods: We measured sublingual microcirculation using incident darkfield video microscopy in 50 subjects on intensive care unit admission after cardiac surgery. Serial measurements of systemic hemodynamics, blood gas, lactate, and catecholamine infusions were recorded each hour for the first 6 h after surgery. Lactate area under the curve (AUC) was calculated over the first 6 h. The lactate AUC was compared between subjects with normal and low perfused vessel density (PVD < 18 mm/mm 2 ), high microcirculatory heterogeneity index (MHI > 0.4), and low vessel-by-vessel microvascular flow index (MFIv < 2.6). Results: Thirteen (26%) patients had a low postoperative PVD, 20 patients (40%) had a high MHI, and 26 (52%) patients had a low MFIv. Patients with low perfused vessel density had higher lactate AUC compared with subjects with a normal PVD (22.3 [9.4–31.0] vs. 2.6 [0–8.8]; P  < 0.0001). Patients with high microcirculatory heterogeneity had a higher lactate AUC compared with those with a normal MHI (2.5 [0.1–8.2] vs. 13.1 [3.7–31.1]; P  < 0.001). We did not find a difference in lactate AUC when comparing high and low MFIv. Conclusion: Low perfused vessel density and high microcirculatory heterogeneity are associated with an increased intensity and duration of lactic acidosis after cardiac surgery with cardiopulmonary bypass. Abstract : Supplemental Digital Content is available in the text